2023
DOI: 10.1101/2023.06.09.544217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using normative models pre-trained on cross-sectional data to evaluate intra-individual longitudinal changes in neuroimaging data

Abstract: Longitudinal neuroimaging studies offer valuable insight into intricate dynamics of brain development, ageing, and disease progression over time. However, prevailing analytical approaches rooted in our understanding of population variation are primarily tailored for cross-sectional studies. To fully harness the potential of longitudinal neuroimaging data, we have to develop and refine methodologies that are adapted to longitudinal designs, considering the complex interplay between population variation and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Different pathogenic CNVs, when combined with environmental influences, could affect individuals differently across various life stages. Ongoing efforts to gather extensive longitudinal samples for developmental periods promise to enrich our normative models significantly 26 . This expansion will demonstrate critical time windows, shedding light on the complex interplay between genetics, environment, and brain function.…”
Section: Addressing Complexities In Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different pathogenic CNVs, when combined with environmental influences, could affect individuals differently across various life stages. Ongoing efforts to gather extensive longitudinal samples for developmental periods promise to enrich our normative models significantly 26 . This expansion will demonstrate critical time windows, shedding light on the complex interplay between genetics, environment, and brain function.…”
Section: Addressing Complexities In Genetic Studiesmentioning
confidence: 99%
“…By employing this approach, z-scores can be calculated for each individual across various neuroimaging modalities, quantifying individual variations against the mean and centiles of population reference norms. Normative models thereby shift focus from group-level to individual-level inferences [22][23][24][25] and allow us to quantify atypical developmental trajectories 26,27 . Normative modeling has proven its efficacy in correlating individual behavioral phenotypes with deviations from reference cohorts, spanning disorders like schizophrenia, autism, and ADHD [28][29][30] and mapping disease progression in Alzheimer's disease 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies applying normative model analysis in schizophrenia are sparse but have shown that abnormal deviations of regional cortical thickness and volume are frequent at the individual level but rarely occur consistently in the same locations and with the same severity across individuals (Wolfers et al, 2018; Lv et al, 2021; Di Biase et al, 2022; Segal et al, 2023). To the best of our knowledge, there are no longitudinal normative modeling studies in individuals with chronic schizophrenia which enable assessment of intra-individual change in deviation between two timepoints and its relation to the established normative range (Di Biase et al, 2023; Barbora Rehák Bučková et al, 2024).…”
Section: Introductionmentioning
confidence: 99%